2002
DOI: 10.1002/1521-4141(200206)32:6<1605::aid-immu1605>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Active tuberculosis in Africa is associated with reduced Th1 and increased Th2 activity in vivo

Abstract: Activation of Th1 lymphocytes, IFN‐γ production and macrophage activation are crucial in defense against Mycobacteria. In developing countries, Th2 activation and IL‐4 production have been associated in vitro with tuberculosis and with poor clinical outcome after treatment. Serological markers of Th1 [soluble lymphocyte activation gene (LAG)‐3] and Th2 (IgE, solubleCD30, and CCL22/macrophage‐derived chemokine) activity were measured in 414 HIV‐negative tuberculosis patients from The Gambia and Guinée and in 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
103
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(123 citation statements)
references
References 35 publications
19
103
0
1
Order By: Relevance
“…The signals that trigger resuscitation of the pathogen prior to reactivation are largely unknown, and it is currently debated whether reactivation is promoted by a shift from type 1 to type 2 cytokines [6], consistent with the observation that the latter cytokines inhibit in vitro production of IFN-c [7]. Several studies have demonstrated that human tuberculosis is paralleled by an increased Th2 response comprising the cytokines IL-4 and IL-13 [8][9][10][11][12], as well as IL-4-dependent IgE secretion [13]. Evidence for Th2 cytokines in murine tuberculosis includes the findings that mycobacterial lipids induce IL-4 production by bone marrow cells [14] and that generation of IgG1 antibody to cardiolipin depends on IL-4 [15].…”
Section: Introductionmentioning
confidence: 90%
“…The signals that trigger resuscitation of the pathogen prior to reactivation are largely unknown, and it is currently debated whether reactivation is promoted by a shift from type 1 to type 2 cytokines [6], consistent with the observation that the latter cytokines inhibit in vitro production of IFN-c [7]. Several studies have demonstrated that human tuberculosis is paralleled by an increased Th2 response comprising the cytokines IL-4 and IL-13 [8][9][10][11][12], as well as IL-4-dependent IgE secretion [13]. Evidence for Th2 cytokines in murine tuberculosis includes the findings that mycobacterial lipids induce IL-4 production by bone marrow cells [14] and that generation of IgG1 antibody to cardiolipin depends on IL-4 [15].…”
Section: Introductionmentioning
confidence: 90%
“…Our results confirm (in mice) earlier reports that IL-4 is generated in the lungs of human TB patients [37][38][39][40]. On the other hand, however, we observed neither an increase in IL-4 expression with disease progression nor the downregulation of Th1 cytokines, associated with this cytokine, reported by Biedermann et al [41].…”
Section: Phasesmentioning
confidence: 99%
“…These T helper 2 (Th2) cytokines also have a protective role during helminth infections but cause susceptibility to bacterial infections like tuberculosis [47]. A geneticand environmental-based balance in Th1/Th2 cytokines could affect the development of infectious and allergic disease.…”
Section: Cytokinesmentioning
confidence: 99%